CHARACTERISTICS OF PATIENTS WITH SNAKEBITES AT SANJIWANI HOSPITAL, BALI - Nindyaswari, Raka Dyah; Masyeni, Sri; Dewi, Saraswati Laksmi; Juwita, Dewa Ayu Putu Ratna (JURNAL WIDYA MEDIKA, 2026)
Snakebites are a common occurrence in tropical regions, including Indonesia. This study aims to determine the demographic and clinical characteristics of patients bitten by snakes. It employs a descriptive, cross-sectional approach to analyze cases at Sanjiwani General Hospital. The sample includes all snakebite cases from January 2021 to December 2022, totaling 192 cases. The results indicate that the majority of snakebite incidents occurred in individuals aged 40-49 years (25.0%), predominantly among males (69.3%), and that most cases originated in Gianyar District (26.6%). The most frequently reported clinical symptom was pain (96.9%), with 91.1% of cases graded 2. Most patients did not experience complications (97.9%). Fang marks were the most common type of wound (96.9%), with the upper extremities being the most frequent bite site (51.6%). Laboratory examinations revealed that the average complete blood count was within the normal range, although prothrombin time (PT) and activated partial thromboplastin time (APTT) were prolonged. The treatments administered included antivenom (99.0%), Human Tetanus Immunoglobulin (94.3%), and antibiotics (99.5%). Notably, all patients in the study survived. The findings highlight the urgent need for targeted public health interventions to educate high-risk populations about snakebite prevention and the importance of seeking prompt medical treatment. Additionally, this study emphasizes the need for improved healthcare resources and training for medical personnel to manage snakebite cases effectively, thereby improving outcomes and reducing complications.